2005
DOI: 10.1021/jp0504571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrogenation Reaction in the Li−Mg−N−H System

Abstract: The Li-Mg-N-H system composed of 3 Mg(NH2)2 and 8 LiH reversibly desorbs/absorbs approximately 7 wt % of H2 at 120-200 degrees C and transforms into 4 Li2NH and Mg3N2 after dehydrogenation. In this work, the mechanism of the hydrogenation reaction from 4 Li2NH and Mg3N2 to 8 LiH and 3 Mg(NH2)2 was investigated in detail. Experimental results indicate that 4 Li2NH is first hydrogenated into 4 LiH and 4 LiNH2. At the next step, 4 LiNH2 decomposes into 2 Li2NH and 2 NH3, and the emitted 2 NH3 reacts with (1/2) Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 23 publications
3
76
0
1
Order By: Relevance
“…As mentioned above, there are two proposals for the dehydrogenation mechanism. Regardless of which mechanism plays the main role, there will be dissociation of the chemical bonds (e.g., NÀH, MgÀN, or LiÀH) of the reactants and the evolution of intermediates (e.g., gas intermediate NH 3 [17][18][19] or complex solid intermediates [15,20,36] ). Therefore, by activating each component of this composite deliberately and looking at the changes in the reaction kinetics, we may be able to clarify the origin of the kinetic barrier.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, there are two proposals for the dehydrogenation mechanism. Regardless of which mechanism plays the main role, there will be dissociation of the chemical bonds (e.g., NÀH, MgÀN, or LiÀH) of the reactants and the evolution of intermediates (e.g., gas intermediate NH 3 [17][18][19] or complex solid intermediates [15,20,36] ). Therefore, by activating each component of this composite deliberately and looking at the changes in the reaction kinetics, we may be able to clarify the origin of the kinetic barrier.…”
Section: Resultsmentioning
confidence: 99%
“…An XRD analysis has confirmed that the above reaction is reversible at 200 °C under 3 MPa of hydrogen [8,17]. However, during dehydrogenation at 250 °C, Aoki et al observed that 5.1 mass% hydrogen had been desorbed [18].…”
Section: Introductionmentioning
confidence: 94%
“…The finding has stimulated much experimental research to enhance the H-storage efficiency. 3 To design high-performance materials, an understanding of basic properties is of great importance. However, the atomic structure of Li 2 NH appears to be controversial.…”
mentioning
confidence: 99%
“…The lattice constant was taken to be the experimental value. The PES on the 32 3 grid was interpolated into a finer grid 88 3 , to obtain converged eigenstates. Each point on the PES was the result of a wave function optimization using DFT.…”
mentioning
confidence: 99%
See 1 more Smart Citation